2021
DOI: 10.36108/laujoces/1202.70.0101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Workability and Compressive Strength of Rice Husk Ash-Blended Palm Kernel Shell Concrete

Abstract: The evaluation of agro-industrial by-products as alternative construction materials is becoming more significant as the demand for environmentally friendly construction materials increases. In this study, the workability and compressive strength of concrete produced by combining Palm Kernel Shell (PKS) and Rice Husk Ash (RHA) was investigated. Concrete mixes using a fixed content of 15% RHA as replacement for cement and 20, 40, 60, 80 and 100% PKS as replacement for crushed granite by volume with the mix ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It ultimately proved that the spores of bacteria were still alive inside the concrete and due to the increment of alkaline ambience they were germinating spores and making the microstructure denser and more compacted. The primary reason behind it is that the hydration rate is relatively low at initial curing ages with bacterial solution and faster at the later ages (Oriola et al, 2018).…”
Section: Ultrasonic Pulse Velocity (Upv) Test Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It ultimately proved that the spores of bacteria were still alive inside the concrete and due to the increment of alkaline ambience they were germinating spores and making the microstructure denser and more compacted. The primary reason behind it is that the hydration rate is relatively low at initial curing ages with bacterial solution and faster at the later ages (Oriola et al, 2018).…”
Section: Ultrasonic Pulse Velocity (Upv) Test Analysismentioning
confidence: 99%
“…Inclusion of Bacillus Megaterium resulted in 24% increment of compressive strength than the conventional concrete samples. Oriola et al (2018) directly applied Bacillus Pumilus bacterial culture in concrete mix as well as used the bacterial culture as a curing agent. The bacterial concrete developed in that study showed a 6.3% increment in compressive strength and also about 4.5% less weight loss than the conventional concrete.…”
Section: Introductionmentioning
confidence: 99%